Why Big Data Matters - Free schools resource to engage young people in health research - Robertson, Sarah; Milbourn, Hannah; Campbell, Archie; Clark, Fiona; Flaig, Robin; Kirby, Liz; Xiao, Xhuoni; Whalley, Heather; Sudlow, Cathie (International Journal of Population Data Science, 2026)
In collaboration with the Schools Health Research Network in Scotland (SHINE), Generation Scotland (GS) developed a free schools resource to educate students about health data and the value of taking part in research, supporting the recruitment of young people to the GS cohort. A scoping exercise with SHINE helped identify needs, and teachers and young people were engaged through their national conference and online focus groups to shape core content. In April 2025, funding from Research Data Scotland enabled revision and expansion of the resource based on teacher feedback. The resulting pack comprises three 45-minute lessons focused on “What is Big Data?” and introduces key concepts in health research, including big data, data linkage and data ethics. The resource was distributed to more than 50 interested schools via various newsletters and partner organisations, reaching schools in 22 of Scotland’s 32 local authorities. Three schools have provided detailed feedback after delivering the lessons to approximately 150–250 pupils each. Offering these lesson plans created a reciprocal relationship that enabled recruitment of young people through schools. Teachers reported that the resource filled a gap in the curriculum, and delivering the lessons alongside GS recruitment materials provided a scalable, sustainable approach by leveraging existing school infrastructure. This not only supported recruitment but also contributed to lasting improvements in students’ health research literacy and understanding of the value of data in research. The resource was developed with input from the SHINE network, extensive teacher feedback and contributions from the GS Young Persons Advisory Group.